Fabrication of Polyvinylpyrrolidone Hydrogel Coated Atomic Force Microscopy Probe by E-beam Irradiation for Dip-pen Nanolithography Patterning. (13th June 2019) - Oh, Sinseok; Kang, Pil-seon; Ha, Tae-Sung; Kim, Kyung-Min; Lim, Jung-Hyurk
Abstract: Dip pen nanolithography (DPN) based on atomic force microscopy (AFM) is a direct-write lithography technology, in which an AFM tip is used to generate nano- or micro-patterns of materials on surfaces. Tip modification has been attracting a good deal of attention to improve the performance of DPN patterning. Herein, we present a new and simple method that uses electron beam irradiation to fabricate a PVP hydrogel polymer coated DPN probe. Using this tip, we generated dot arrays of fluorescent materials and measured patterns by AFM and fluorescence microscopy.